Real-time process dynamics monitoring in Anammox reactors - KOCAMEMİ, BİLGE (IWA PUBLISHING, 2014)
Process dynamics in Anammox systems were evaluated through continuous monitoring of pH, oxidation reduction potential (ORP) and conductivity in two separate newly started-up sequencing batch reactors, one seeded with an enriched Anammox sludge and the other seeded with mixed activated sludge. The pH and ORP profiles exhibited characteristic patterns depending on the process dynamics during early start-up, start-up and enrichment phases of the operational period of 410 days. The simultaneously continuing processes of the start-up period showed apparent indicative trend lines in pH and ORP profiles. Conductivity profiles were consistent with the process dynamics in all phases. During the enrichment phase, conductivity decreases could quantitatively be related to process removal efficiencies and all real-time profiles exhibited specific break-points which coincided with the end of Anammox in each cycle. The end of Anammox was observed as an 'apex' on pH profiles and a 'valley' on ORP profiles. The 'apex' and 'valley' points exactly coincided with the end point of the linear decrease in the conductivity profiles. The overall findings suggested a great potential in using real-time pH, ORP and conductivity measurements for quick and reliable monitoring of Anammox systems during start-up and enrichment periods.
Keywords: Anammox; conductivity; enrichment; ORP; pH; start-up; SEQUENCING BATCH REACTOR; AMMONIUM OXIDATION; BACTERIA